The Combination Test Between of Waste Mushroom Logs, Cow Manure Fertilizer and Decomposers to Growth and Yield Of Red Onions (Allium cepa car philipine) - Septia, Erfan Dani; Wahyudiningtyas, Andiny Dwi (Universitas Muhammadiyah Malang, 2019)
Red onion production can be increased by fertilization. Fertilization serves to provide nutrients for plant growth. Chemical fertilizer provides a bad impact on the environment in the long term so that the application of organic fertilizer can be a recommendation. Organic fertilizers are fertilizers derived from animal matter, animal manure, human excreta, and vegetable matter (e.g. compost and crop residues). Waste mushroom logs, cow manure fertilizer, and decomposers used in this research. All of the matter in this research can be a source of nutrients for growing plants and an increase of production and yield of red onions. The objective of this research was to study the combination test between of waste mushroom logs, cow manure fertilizer, and decomposers to growth and yield of red onion. This research was arranged in a Randomized Block Design (RBD), where the main plot is cow manure fertilizer and waste mushroom log, the subplot in the form of a decomposer. The results showed that there was not interaction between cow manure fertilizer and decomposer waste on all parameters of observed growth and yield of red onion. Special decomposer real treatment of the growth of the number of leaves of plant ages 15 HST (18.98), 20 HST (20.33), 25 HST (23.47), 30 HST (25.76), and 35 HST (26.11), and plant height is 35 HST (33.21 cm). The treatment of waste mushroom logs 100% produces a relatively large number of tubers compared to others, which is 8.89 tubers.